Financial Factors and Non-Financial to Financial Distress Insurance Companies That Listed in Indonesia Stock Exchange - Liahmad Liahmad; Kartika Rusnindita; Yuni Putri Utami; Saleh Sitompul (Budapest International Research and Critics University, 2021)
This study aims to test the influence of financial factors in the form of liquidity, cash flow, company size, institutional ownership, earnings and the factors of non-financial form of the independent commissioner against the financial distress of insurance companies that listed in Indonesia stock Exchange. The population of this research as many as 17 of the insurance company. The sampling technique using purposive sampling method, so that the obtained 15 sample company for 4 years of observations of the years 2017 - 2020, with 60 observations of the study. Data analysis using descriptive statistical analysis and logistic regression analysis. The results show that liquidity, cash flows, institutional ownership and independent commissioner does not affect significantly to financial distress, while the method of the size of the company and profit and significant effect on financial distress.